The Relationship of Self-Concept to Students’ Interpersonal Communication - Desmi Nadia; Yusri Yusri; Zadrian Ardi (Jurnal Neo Konseling, 2020)
This research is motivated by the phenomenon in the field still found students who have low interpersonal communication in following the learning process. One factor that causes interpersonal communication is that not all students are able to make effective communication in the learning process and the lack of self-concept students have. This study aims to look at the general picture of students' interpersonal communication, self-concept. Test the relationship of self-concept to students' interpersonal communication. This research is a descriptive correlational study. With a sample of 102 students selected using a sampling technique chosen by simple random sampling technique. Data collection using self-concept questionnaire and student interpersonal communication with Likert scale model. The results of this study indicate: (1) self-concept is in the high category with a score of 47 and the percentage of 46.1%, (2) interpersonal communication is in the moderate category with a score of 89 and the percentage of 87.3% (3) there is a significant positive relationship between self concept with interpersonal communication with rxy = 0.439 and a significant level of 0,000. The findings of this study can be a reference for BK teachers in making programs to provide BK services to students.